History of modern South Asia : Politics, states, diasporas - Talbot, Ian (New Haven : Yale University Press, 2016)
Noted historian Ian Talbot has written a new history of modern South Asia that considers the Indian Subcontinent in regional rather than in solely national terms. A leading expert on the Partition of 1947, Talbot focuses here on the combined history of India, Pakistan, and Bangladesh since 1757 and specifically on the impact of external influences on the local peoples and cultures. This text explores the region$1 (Bs colonial and postcolonial past, and the cultural and economic Indian reaction to the years of British authority, thus viewing the transformation of modern South Asia through the lens of a wider world.s
Keywords: South Asia -- History; History / Asia / South / General; History / Modern / 19th Century; History / Asia / India & South Asia